Studi Empiris: Perilaku Konsumen Terhadap Media Sosial Industri Bakpia Di Daerah Istimewa Yogyakarta - Riscky, Ibnu Dwi Nur; Astuti, Budi (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study aims to examine the influence of social media marketing on repurchase intention through brand trust and brand image. The quantitative approach was applied by distributing questionnaires to 310 respondents of Bakpia MSME customers in the Special Region of Yogyakarta. Data analysis was conducted using AMOS 23 software with SEM modeling and Sobel Test. The results showed that social media marketing has a positive effect on repurchase intention, brand trust, and brand image. Brand image has a positive effect on brand trust. Brand trust and brand image have a positive effect on repurchase intention. Social media marketing has a positive effect on repurchase intention mediated by brand trust and brand image. These findings provide important implications for Bakpia UMKM managers in Yogyakarta by utilizing social media in building stronger relationships with customers to improve brand image and brand trust, and encourage repeat purchase interest.